KARAKTERISTIK TANAH PADA LAHAN BEKAS TAMBANG DENGAN UMUR REVEGETASI YANG BERBEDA - , ROFITA SP; , Prof. Dr. Ir. Supriyanto Notohadisuwarno, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Soil characteriristic studies on the mined land revegetation of different ages, aiming to identify the effect of rehabilitation on morphological properties, physical and chemical properties of soil disposal (deposits) in mining area of PT. Nusa Halmahera Minerals. The study began in August 2010 and ended in September 2011 and carried out in three stages, namely, field research, laboratory analysis, and descriptive data analysis. At the post mined areas, namely Gosowong and Toguraci, investigation were conducted through five soil profile under less than 1 year, 3 years, 6 years, and 9 years revegetation condutions, respectively. As a comparison a profile under natural forest nearly was also described. Parameters of soil morphology observed in the field include soil color, soil structure, consistency, while the physical and chemical parameters of soil properties in the analysis that includes gravity, heavy volume, total porosity, aggregate stability, pH, organic C, total N, organic matter, available-K, CEC, and exchangeable-Al. The results showed that the revegetation area has a relief with a slope of 20-25%. Vegetation cover is very diverse, with a percentage of the closure of land, where the revegetation of land that is less than 1 year old has a level of 40% coverage, 3 years 65%, 6 years 80%, 95% 9 years, while the natural forest 100% coverage, with dominant vegetation type of Paraserianthes sp, Albizzia falcataria , Acacia auriculiformis, Octomeles sumatrana, and Imperata cylindrical. While the results of analysis of soil physical properties of the five profiles of the study very high variations in texture class that was sandy clay loam, clay loam, loam and clay, BV values ranged from 0.89 to 1.52 g / cm Â³, BJ values ranged between 2.29 up to 2.59 g / cm Â³, total porosity ranges between 39.43 to 61.26%, aggregate stability ranged from 30.74 to 72.49%, while for the chemical properties of soil has a pH in the fifth profile (H2O) ranged from 3.29, to 6.00, organic C ranged from 0.33 to 4.25%, total-N ranged from 0.02 to 0.29%, organic matter ranges from 0.56 to 7.33%, available-K ranged from 0.15 to 0.60 (cmol (+) kg-1), CEC ranged from 3.30 to 6.90 (cmol (+) kg-1), exchangeable-Al ranged from 0.04 to 10, 18 (cmol (+) kg-1). The longer the age of revegetation, the increased levels of organic matter, total- N, organic C, porosity, and available-K in the soil, and the more weight and volume weight of soil types.